2014
DOI: 10.1371/journal.pone.0105317
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Subgenotype A1: Evolutionary Relationships between Brazilian, African and Asian Isolates

Abstract: Brazil is a country of low hepatitis B virus (HBV) endemicity in which the genotype A of HBV (HBV/A) is the most prevalent. The complete nucleotide sequences of 26 HBV/A isolates, originating from eight Brazilian states, were determined. All were adw2. Twenty-three belonged to subgenotype A1 and three to A2. By phylogenetic analysis, it was shown that all the 23 HBV/A1 isolates clustered together with isolates from Bangladesh, India, Japan, Nepal, the Philippines and United Arab Emirates, but not with those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 54 publications
8
49
0
8
Order By: Relevance
“…A study in Haiti suggests that A1 was introduced from eastern Africa to Haiti during the slave trade around the turn of the 18th century . Another study in Brazil revealed the close relatedness of the Brazilian, Asian and Somalian isolates and suggests that the Brazilian A1 strains originate from South‐East Africa at the middle of the 19th century . Moreover, in the recent subgenotype A1 of HBV‐tracing human migrations in and out of Africa, the coclustering of Somalian and Latin American strains and the plausible sites of A1 origin and dispersal routes to Asia and Latin America are presented .…”
Section: Discussionmentioning
confidence: 99%
“…A study in Haiti suggests that A1 was introduced from eastern Africa to Haiti during the slave trade around the turn of the 18th century . Another study in Brazil revealed the close relatedness of the Brazilian, Asian and Somalian isolates and suggests that the Brazilian A1 strains originate from South‐East Africa at the middle of the 19th century . Moreover, in the recent subgenotype A1 of HBV‐tracing human migrations in and out of Africa, the coclustering of Somalian and Latin American strains and the plausible sites of A1 origin and dispersal routes to Asia and Latin America are presented .…”
Section: Discussionmentioning
confidence: 99%
“…These two genotypes are commonly detected in Brazil . The genotype A1 was brought to America during the slave trade, so it was commonly found in African descendants . The genotype F2 is Native American with origins in indigenous populations .…”
Section: Discussionmentioning
confidence: 99%
“…16,26,34,35 The genotype A1 was brought to America during the slave trade, so it was commonly found in African descendants. 17,35 The genotype F2 is Native American with origins in indigenous populations. 34,36 The viral loads found in the three samples submitted for quantification of DNA did not represent a significant risk for developing cirrhosis and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Широкое распростране-ние ВГВ субтипа A1 описано также в Бразилии, что, по всей видимости, является следствием бо-лее поздней «миграционной» волны, так как вы-является преимущественно у чернокожих и му-латов [8], подтверждая предположение о завозе вируса с пленниками, вывезенными из Юго-Восточной Аф рики в середине XIX в. [14].…”
Section: результаты и обсуждениеunclassified